APPLICATION OF THE K-MEAN ALGORITHM IN DETERMINING THE RIGHT PROFESSION FOR INFORMATION TECHNOLOGY STUDENTS - Assyafiq, Dhia Marsya; Mulyani, Astriana (Journal of Information System, Informatics and Computing; Vol 7 No 2 (2023): JISICOM (December 2023), 2023)
This research focuses on interests in the right field of work for information technology students majoring in Informatics. Many graduate students majoring in informatics work not in accordance with the knowledge taken during lectures. Of course this causes problems in determining alumni who work in accordance with the knowledge pursued. From these problems this research is to determine the right job for information technology students, especially informatics majors, help students make decisions in determining the appropriate field of work and help focus student learning so that the field of work is passionate and the efforts made are in accordance with the chosen path. The method used in this research is to collect data on the field of work that is in accordance with the information technology major obtained from making observations, giving questionnaires and conducting literature studies. The data obtained is processed using the K-Means algorithm. The K-Means algorithm is a method of grouping data by grouping data into different groups in an iterative manner, by minimizing the average distance of the data to each group. The results of the study show the results of grouping the data into different groups from the data groups with low, medium and high interest. In this case it can be concluded that the resulting data can help computer engineering students determine the field of work.